Enhancing the thermal conductivity of carbon fiber reinforced polymer composite laminates by coating highly oriented graphite films. (25th December 2015) - Yu, Guo-Cai; Wu, Lin-Zhi; Feng, Li-Jia
Abstract: This paper focus on utilizing a simple and effective method that is coating highly oriented graphite films (HOGFs) on the surface of polyacrylonitrile-based (PAN-based) carbon fiber reinforced plastic (CFRP) composite laminates to improve the in-plane thermal conductivity of composite laminates. The thermal physical and mechanical properties of HOGF reinforced CFRP (HOGF-CFRP) composite laminates are measured. The measurement results show that HOGF greatly improves the in-plane thermal conductivity of hybrid HOGF-CFRP composite laminates. In-plane thermal conductivity of HOGF-T700/epoxy composite laminates increases to 50.7 W/m K and enhances 14.1 times than that of T700/epoxy composite laminates. The in-plane thermal conductivity of HOGF-M55J/epoxy hybrid composite laminates is also up to 118.8 W/m K and attains to the level of the aluminum alloys (nearly 120 W/m K), which satisfy the requirement of engineering application in aircraft, aerospace and other high-end heat dissipation fields. Moreover, HOGF-CFRP composite laminates show the same low thermal expansivity as CFRP composite laminates. The mechanical results suggest that the HOGF-CFRP composite laminates not only have high in-plane thermal conductivity but also high specific mechanical property. Graphical abstract: Highlights: An effective method coating HOGF improves the thermal conductivity of composites. In-plane thermal conductivities of hybrid composites show a significant increase. HOCF-CFRP composite laminates have high specific strength and specific modulus. New hybrid composite laminates show the advantage of low cost.